Effects of Nutrition Education and Exercise Programs on Perceived Dietary Behaviors, Food Intake and Serum Lipid Profiles in Elderly Korean Women Living in Residential Homes - Hee-Seon Kim, PhD; Kyung-Ja June, RN, PhD; Rhayun Song, RN, PhD (Elsevier, 2007)
Strong predictors for the risk of cardiovascular disease in older adults include levels of total cholesterol, low-density lipoprotein cholesterol, and high-density lipoprotein cholesterol, which can be modified by dietary behavioral changes and regular physical exercise. The purpose of this study was to evaluate changes in perceived dietary behaviors, food intake, and serum lipid profiles after providing a nutrition education and exercise program to elderly women living in residential homes. Methods: The nutrition education classes and supervised Korean dance exercise classes (four times per week) were provided for 10 weeks to 64 elderly women from residential homes in Korea. Subjects were interviewed to assess perceived dietary behaviors, food intake by 24-hour recall, and fasting blood samples were obtained before and after the program and at a 3-month follow-up. Results: Initially, the intakes of vitamin A, vitamin C, riboflavin and calcium of our subjects were insufficient. After the program, the actual food intake and perceived dietary behaviors were significantly improved, but had declined back to baseline levels by the 3-month follow-up. The index of nutritional quality and serum lipid profiles were significantly improved after the program, and they remained significant at the 3-month follow-up. Conclusion: The nutrition education and exercise program for institutionalized elderly women was effective in leading to positive changes shortly after the program, but the effects only partially remained at the 3-month follow-up. A health promotion program designed for an elderly population should consider strategies of motivating them to initiate a healthy lifestyle and subsequently maintain improvements in dietary behavior-related health in the long term.